Community Awareness of HPV Screening and Vaccination in Odisha. (9th December 2015) - Khanna, Niharika; Ramaseshan, Aparna; Arnold, Stephanie; Panigrahi, Kalpana; Macek, Mark D.; Padhi, Bijaya K.; Samanta, Diptirani; Senapati, Surendra N.; Panigrahi, Pinaki
Abstract : Introduction . A number of new technologies including cervical cancer screening and vaccination have introduced new tools in the fight against cervical cancer. Methods . This study was set in Odisha, India, at the Acharya Harihar Regional Cancer Center and study research infrastructure at the Asian Institute of Public Health. IRB approvals were obtained and a research assistant recruited 286 women aged 18–49 years, who provided informed consent and completed a survey tool. Data were entered into EpiData software and statistical analysis was conducted. Results . 76.3% women participants were married, 45.5% had sexual debut at age 21 or greater, 60.5% used contraception, 12.2% reported having a Pap smear in the past, and 4.9% reported having prior genital warts. Most, 68.8% had never heard of HPV and 11.9% were aware that HPV is the main cause of cervical cancer. 82.9% women thought that vaccinations prevent disease, and 74.8% said they make the decision to vaccinate their children. Conclusion . The Odisha community demonstrated a low level of knowledge about cervical cancer prevention, accepted vaccinations in the prevention of disease and screening, and identified mothers/guardians as the key family contacts.